Evaluation of Metacognitive Functions and Clinical Characteristics of the Patients Diagnosed with Obsessive Compulsive Disorder and Delusional Disorder - Çağlar, Neslihan; Özsoy, Filiz; Mermi, Osman (Rabia YILMAZ, 2016)
Our study aims to evaluate metacognitive functions and clinical characteristics of the patients diagnosed with Obsessive Compulsive Disorder (OCD) and Delusional Disorder (SB) in comparison with the control group . Patients, complying with the inclusion criteria, were chosen from inpatients and outpatients admitted to Fırat University Hospital, Mental Health and Illness Clinic. 50 patients with Obsessive Compulsive Disorder (OCD) and 40 patients with Delusional Disorder (DD) and 50 healthy controls who were matched with patient groups in terms of age and gender were included into study. Structured Clinical Interview Scale for DSM-IV Axis I Disorders (SCID-I), sociodemographical and clinical interview form, metacognition assessment scale -30 (MAS), for OCD patient group additionally Yale-Brown Obsessions and Compulsions Inventory (Y–BOCS) and Obsessive Beliefs Questionnaire-44 (OBQ-44), for DD patients the Brief Psychiatric Rating Scale (BPRS) and Beck Cognitive Insight Scale (BCIS) were administered to patient and control groups. As a result, although metacognition total scores of OCD and DD patients were higher than control group, statistically significant results were determined merely in OCD patients. In OCD patients metacognition uncontrollability and danger together with control need sub dimensions, in DD patients cognitive confidence sub dimension were statistically significant in comparison to control group. Moreover, in OCD patients a positive correlation between Y–BOCS’s sub dimension evaluating compulsions and control need, between OBQ-44’s sub dimensions perfectionism/precision uncontrollability danger; in DD patients a positive correlation between BCIS’s self-expression and cognitive confidence, self-assurance and positive belief sub dimensions were detected. Results of our study put forward that OCD and DD patient groups and control group present differences in terms of MAS parameters. More and more researches need to be carried out in order to determine casual relation between these differences and OCD and DD illnesses.Our study aims to evaluate metacognitive functions and clinical characteristics of the patients diagnosed with Obsessive Compulsive Disorder (OCD) and Delusional Disorder (SB) in comparison with the control group .Patients, complying with the inclusion criteria, were chosen from inpatients and outpatients admitted to Fırat University Hospital, Mental Health and Illness Clinic. 50 patients with Obsessive Compulsive Disorder (OCD) and 40 patients with Delusional Disorder (DD) and 50 healthy controls who were matched with patient groups in terms of age and gender were included into study.Structured Clinical Interview Scale for DSM-IV Axis I Disorders (SCID-I), sociodemographical and clinical interview form, metacognition assessment scale -30 (MAS), for OCD patient group additionally Yale-Brown Obsessions and Compulsions Inventory (Y–BOCS) and Obsessive Beliefs Questionnaire-44 (OBQ-44), for DD patients the Brief Psychiatric Rating Scale (BPRS) and Beck Cognitive Insight Scale (BCIS) were administered to patient and control groups.As a result, although metacognition total scores of OCD and DD patients were higher than control group, statistically significant results were determined merely in OCD patients. In OCD patients metacognition uncontrollability and danger together with control need sub dimensions, in DD patients cognitive confidence sub dimension were statistically significant in comparison to control group. Moreover, in OCD patients a positive correlation between Y–BOCS’s sub dimension evaluating compulsions and control need, between OBQ-44’s sub dimensions perfectionism/precision uncontrollability danger; in DD patients a positive correlation between BCIS’s self-expression and cognitive confidence, self-assurance and positive belief sub dimensions were detected.Results of our study put forward that OCD and DD patient groups and control group present differences in terms of MAS parameters. More and more researches need to be carried out in order to determine casual relation between these differences and OCD and DD illnesses.

Çalışmamızda; Obsesif Kompulsif Bozukluk (OKB) ve Sanrılı Bozukluk (SB) tanısı alan hastaların üstbiliş işlevlerinin ve klinik özelliklerinin kontrol grubuyla karşılaştırılarak değerlendirilmesi amaçlanmıştır. Çalışmaya Fırat Üniversitesi Hastanesi Ruh Sağlığı ve Hastalıkları Polikliniğine başvuran yatarak ya da ayaktan tedavi gören ve çalışma ölçütlerine uyan, OKB tanılı 50 hasta, SB tanılı 40 hasta ile hasta gruplarıyla yaş ve cinsiyet açısından eşleştirilmiş 50 sağlıklı kontrol alınmıştır. Hasta ve kontrol grubuna DSM–IV Eksen–I Bozuklukları için Yapılandırılmış Klinik Görüşme Ölçeği (SCID–I), Sosyodemografik ve Klinik Veri Formu, Üstbiliş Ölçeği-30 (ÜBÖ), OKB hasta grubuna ek olarak Yale-Brown Obsesyon Kompulsiyon Ölçeği (Y-BOKÖ) ile Obsesif İnanışlar Ölçeği 44 (OİÖ-44), SB hastalarına ise Kısa Psikiyatrik Değerlendirme Ölçeği (KPDÖ) ile Beck Bilişsel İçgörü Ölçeği (BBİÖ) uygulanmıştır. Sonuç olarak; OKB ve SB hastalarının, üstbiliş toplam puanları kontrol grubuna göre yüksekti fakat istatistiksel olarak anlamlı sonuçlar sadece OKB hastalarında saptandı. OKB hastalarında; üstbiliş kontrol edilmezlik tehlike ile kontrol ihtiyacı alt boyutları, SB hastalarında ise; bilişsel güven alt boyutu kontrol grubuna kıyasla istatistiksel olarak anlamlı bulunmuştur. Ayrıca OKB hastalarında; Y-BOKÖ’nin kompulsiyonları değerlendiren alt boyutu ile kontrol ihtiyacı, OİÖ-44’ün mükemmeliyetçilik/kesinlik ile kontrol edilmezlik tehlike alt boyutları arasında, SB hastalarında ise; BBİÖ’nin kendini ifade etme ile bilişsel güven ve kendinden eminlik ile olumlu inanç alt boyutları arasında pozitif korelasyon saptanmıştır. Araştırmamızın sonuçları; OKB ve SB hasta grupları ile kontrol grubunun ÜBÖ parametreleri açısından farklılıklar gösterdiğini ortaya koymuştur. Bu farklılıklar ile OKB ve SB hastalıklarının nedensel ilişkisini saptamaya yönelik daha fazla sayıda çalışmaya gereksinim vardır.Çalışmamızda; Obsesif Kompulsif Bozukluk (OKB) ve Sanrılı Bozukluk (SB) tanısı alan hastaların üstbiliş işlevlerinin ve klinik özelliklerinin kontrol grubuyla karşılaştırılarak değerlendirilmesi amaçlanmıştır.Çalışmaya Fırat Üniversitesi Hastanesi Ruh Sağlığı ve Hastalıkları Polikliniğine başvuran yatarak ya da ayaktan tedavi gören ve çalışma ölçütlerine uyan, OKB tanılı 50 hasta, SB tanılı 40 hasta ile hasta gruplarıyla yaş ve cinsiyet açısından eşleştirilmiş 50 sağlıklı kontrol alınmıştır. Hasta ve kontrol grubuna DSM–IV Eksen–I Bozuklukları için Yapılandırılmış Klinik Görüşme Ölçeği (SCID–I), Sosyodemografik ve Klinik Veri Formu, Üstbiliş Ölçeği-30 (ÜBÖ), OKB hasta grubuna ek olarak Yale-Brown Obsesyon Kompulsiyon Ölçeği (Y-BOKÖ) ile Obsesif İnanışlar Ölçeği 44 (OİÖ-44), SB hastalarına ise Kısa Psikiyatrik Değerlendirme Ölçeği (KPDÖ) ile Beck Bilişsel İçgörü Ölçeği (BBİÖ) uygulanmıştır.Sonuç olarak; OKB ve SB hastalarının, üstbiliş toplam puanları kontrol grubuna göre yüksekti fakat istatistiksel olarak anlamlı sonuçlar sadece OKB hastalarında saptandı. OKB hastalarında; üstbiliş kontrol edilmezlik tehlike ile kontrol ihtiyacı alt boyutları, SB hastalarında ise; bilişsel güven alt boyutu kontrol grubuna kıyasla istatistiksel olarak anlamlı bulunmuştur. Ayrıca OKB hastalarında; Y-BOKÖ’nin kompulsiyonları değerlendiren alt boyutu ile kontrol ihtiyacı, OİÖ-44’ün mükemmeliyetçilik/kesinlik ile kontrol edilmezlik tehlike alt boyutları arasında, SB hastalarında ise; BBİÖ’nin kendini ifade etme ile bilişsel güven ve kendinden eminlik ile olumlu inanç alt boyutları arasında pozitif korelasyon saptanmıştır.Araştırmamızın sonuçları; OKB ve SB hasta grupları ile kontrol grubunun ÜBÖ parametreleri açısından farklılıklar gösterdiğini ortaya koymuştur. Bu farklılıklar ile OKB ve SB hastalıklarının nedensel ilişkisini saptamaya yönelik daha fazla sayıda çalışmaya gereksinim vardır.
SANRILI BOZUKLUK VE OBSESİF KOMPULSİF BOZUKLUK HASTALARINDA ÜSTBİLİŞ İŞLEVLERİNİN DEĞERLENDİRİLMESİ
Keywords: Health Care Administration; Sağlık Kurumları Yönetimi